2010
DOI: 10.1017/s0022377810000280
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of dust particles by vortex ring

Abstract: It is shown that nonlinear interaction between large amplitude circularly polarized EM wave and dusty plasma leads to a nonstationary ponderomotive force which in turn produces a vortex ring, and magnetic field. Then the ensuing vortex ring in the direction of propagation of the pump wave can accelerate the micron-size dust particles which are initially at rest and eventually form a non relativistic dust jet. This effect is purely nonstationary and unlike linear vortices, dust particles do not rotate here. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Despite a history spanning nearly a century, research into complex (dusty) plasmas has advanced tremendously over the last two decades both academically and due to its variety of applications in space and modern astrophysics, semiconductor technology, fusion devices, plasma chemistry etc [1][2][3][4][5][6][7][8][9]. Some of the novel experimental discoveries that have been made are dusty plasma crystals, dust Mach cones, dust voids [8,9], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a history spanning nearly a century, research into complex (dusty) plasmas has advanced tremendously over the last two decades both academically and due to its variety of applications in space and modern astrophysics, semiconductor technology, fusion devices, plasma chemistry etc [1][2][3][4][5][6][7][8][9]. Some of the novel experimental discoveries that have been made are dusty plasma crystals, dust Mach cones, dust voids [8,9], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Vortex rings are found in a range of other phenomena, including tornado and hurricane structures, interstellar media, 14 dilute atomic Bose–Einstein condensates, 15 tokomaks, 16 and the growth of single-wall carbon nanotubes. 17 Moffatt 18 gave an asymptotic solution for flow in a vortex ring without swirl and showed that a solution must exist for a vortex ring with swirl.…”
Section: Introductionmentioning
confidence: 99%